2007
DOI: 10.1183/09031936.00086306
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in COPD patients with low body mass index

Abstract: Patients with chronic obstructive pulmonary disease (COPD) show abnormal adaptations of skeletal muscle redox status after exercise training. Increased skeletal muscle oxidative stress in COPD patients may prompt mitochondrial dysfunction.The present study explores the association between body composition and mitochondrial respiration in seven COPD patients with low body mass index (BMIL), eight COPD patients with normal body mass index (BMIN) and seven healthy controls. All of them underwent a vastus laterali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 51 publications
5
119
0
3
Order By: Relevance
“…Data regarding expression of inflammatory genes in relation to NF-kB activation are, however, lacking. Furthermore, some studies reported increased levels of inflammatory markers, including tumour necrosis factor (TNF)-a protein, in skeletal muscle of COPD patients [36,37], while others did not [38]. This discrepancy may be related to differences in COPD phenotypes and muscles studied.…”
Section: Ppars and Regulation Of Skeletal Muscle Functionmentioning
confidence: 88%
“…Data regarding expression of inflammatory genes in relation to NF-kB activation are, however, lacking. Furthermore, some studies reported increased levels of inflammatory markers, including tumour necrosis factor (TNF)-a protein, in skeletal muscle of COPD patients [36,37], while others did not [38]. This discrepancy may be related to differences in COPD phenotypes and muscles studied.…”
Section: Ppars and Regulation Of Skeletal Muscle Functionmentioning
confidence: 88%
“…Accordingly, we read with great interest the article by RABINOVICH et al [2], which was recently published in the European Respiratory Journal. RABINOVICH et al [2] showed that chronic obstructive pulmonary disease (COPD) patients with a low body mass index (BMI; 19.2¡0.6 kg?m -2 ) have a dysfunctional mitochondrial electron transport chain in comparison with COPD patients with a ''normal'' BMI (29.0¡1.7 kg?m -2 ) and healthy controls (27.9¡1.9 kg?m -2 ). The function of the mitochondrial electron transport chain was assessed as acceptor control ratio (i.e.…”
Section: Mitochondrial Dysfunction In Copd Patients With Low Body Masmentioning
confidence: 97%
“…In the study performed by RABINOVICH et al [2], the prevalence of current and past smoking was not reported. As a consequence, the potential influence of smoking on the outcome of the study was neither analysed nor discussed.…”
Section: Mitochondrial Dysfunction In Copd Patients With Low Body Masmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with COPD have a significantly lower mitochondrial density 33 and activity 34 , as well as a lower oxidative enzyme activity 35 and a lower mechanical efficiency 36 . There are also fewer capillaries per muscle fiber in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%